Are satisfaction and performance of meaningful activities associated with frailty in older adults?. (February 2023) - Akaida, Shoma; Tabira, Takayuki; Nakai, Yuki; Maruta, Michio; Taniguchi, Yoshiaki; Tomioka, Kazutoshi; Sato, Nana; Wada, Ayumi; Makizako, Hyuma
Highlights: Investigated the association between meaningful activities and frailty based on sex. Activity satisfaction was associated with frailty in men. Activity satisfaction and performance were associated with frailty in women. Prevention of frailty may play a positive role in meaningful activities.